Apostolepis multicincta Harvey 1999 (Squamata, Dipsadidae) in Argentina - Burgos Gallardo, Freddy (2017)
Apostolepis multicincta, a fossorial snake known only from Bolivia, is recorded in Argentina, extending its known range 450 km south of the previous closest record.